LOYALITAS PELANGGAN DITINJAU DARI STORE ATMOSPHERE, KEMUDAHAN DAN KEPERCAYAAN STUDI PADA J&T EXPRESS SURAKARTA - Davit Mirwan Itsnaini; Istiatin Istiatin; Bambang Mursito (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to prove simultaneously and partially customer loyalty in terms of store atmosphere, convenience and trust in J&T Express Surakarta. This research is descriptive quantitative. The population is all J&T Express Surakarta service users. The number of samples used according to Sugiyono's guidelines, amounting to 100 respondents, the sample was taken by using purposive sampling technique. The data analysis technique used in this study is multiple linear regression analysis. The conclusion of this study is that store atmosphere, convenience and trust have a significant effect on consumer loyalty of J&T Express Surakarta. Keywords : Store Atmosphere, Convenience, Trust.